Media Management in Mali: Impact of Journalists' Economic Precarity on the Quality of Information in Print Media - (:unkn) unknown (My University, 2024)
Exploring the impact of economic precarity on the quality of journalism in Mali, this pioneering study aims to decipher the repercussions of economic conditions on journalistic practices and information dissemination in a specific African context. By adopting a mixed methodology, combining qualitative analyses through semi-structured interviews with 384 media industry stakeholders, and quantitative analysis via linear regressions, this research provides a comprehensive perspective on the interaction between economic precarity and journalism. The results reveal a notable correlation between economic precarity and the decline in information quality, affecting media objectivity and varying according to journalistic genres, in line with theories of professional precarity and media gatekeeping. However, the specificity of the Malian context and the focus on the print press limit the scope of the conclusions. The practical implications of this study highlight the urgency of investing in journalist training and adopting more equitable media regulation. Making a significant contribution to understanding the challenges of media in developing countries, this article offers valuable insights into the interaction between economy and journalism, enriching the debate on information quality in precarious environments.Keywords: Economic Precarity; Journalism; Mali; Media; Print PressClassification Jel : L82 ; J44 ; O17 ; M12 ; Z13Type d’article : Empirical recherch
Keywords: African Research